High Power Energy Storage via Electrochemically Expanded and Hydrated Manganese-Rich Oxides - Boyd, Shelby; Geise, Natalie R.; Toney, Michael F.; Augustyn, Veronica (Frontiers in Chemistry, 2020)
Understanding the materials design features that lead to high power electrochemical energy storage is important for applications from electric vehicles to smart grids. Electrochemical capacitors offer a highly attractive solution for these applications, with energy and power densities between those of batteries and dielectric capacitors. To date, the most common approach to increase the capacitance of electrochemical capacitor materials is to increase their surface area by nanostructuring. However, nanostructured materials have several drawbacks including lower volumetric capacitance. In this work, we present a scalable “top-down” strategy for the synthesis of EC electrode materials by electrochemically expanding micron-scale high temperature-derived layered sodium manganese oxides. We hypothesize that the electrochemical expansion induces two changes to the oxide that result in a promising electrochemical capacitor material: (1) interlayer hydration, which improves the interlayer diffusion kinetics and buffers intercalation-induced structural changes, and (2) particle expansion, which significantly improves electrode integrity and volumetric capacitance. When compared with a commercially available activated carbon for electrochemical capacitors, the expanded materials have higher volumetric capacitance at charge/discharge timescales of up to 40 seconds. This shows that expanded and hydrated manganese-based oxide powders are viable candidates for electrochemical capacitor electrodes.